Vocational interest profile by candidates of Job and Occupation Consultants - Zülfikar DENİZ Kaan (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
This study was conducted in accordance with certain objectives and some of them are to determine the interest of these individuals especially in the psychological aspect of this profession, to examine the difference between their interests on the basis of gender, to learn their opinions about their department and why they want to become a JOC. The participants of this study were the JOC candidates who attended 360 hours Job and Occupation Consultancy training at Ankara University. The participant group composed of 216 individuals, while 140 of them were female, 73 of them were male. Also 3 participants did not specified their gender. The data of this study were collected by means of Occupational Field Interest Inventory (OFII) that was administered in classroom setting and certain questions were attached to this inventory. The data were analyzed using Pearson correlation formula, independent samples t test and descriptive statistics. As a result of the study, significant differences were found to be high in the advantage of male participants in Computer, Engineering, Political - Financial Sciences areas and in the advantage of female participants in Psychology, Visual Arts and Health areas, similarly in the literature. While only 14% of the participants stated that they wanted to study psychology by taking into account their interests, it was rated above the average from interest sub-set of 60% of them